The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cryst11070753
|View full text |Cite
|
Sign up to set email alerts
|

Study of Corrosion Resistance and Degradation Mechanisms in LiTiO2-Li2TiO3 Ceramic

Abstract: The interest in lithium-containing ceramics is due to their huge potential as blanket materials for thermonuclear reactors for the accumulation of tritium. However, an important factor in their use is the preservation of the stability of their strength and structural properties when under the influence of external factors that determine the time frame of their operation. This paper presents the results of a study that investigated the influence of the LiTiO2 phase on the increasing resistance to degradation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Given that the crystal structure and transition-metal (Ti or Mn) oxidation state of m -Li 2 TiO 3 (β phase) are similar to those of m -Li 2 MnO 3 , we considered whether m -Li 2 TiO 3 could be formed as a secondary phase in o -LiMn 1– x Ti x O 2 ( x = 0.05, 0.1). However, according to the literature, c -Li 2 TiO 3 (γ phase) is more stable than m -Li 2 TiO 3 at high temperatures (≤1050 °C). , In addition, there are a significant number of oxygen vacancies in o -LiMn 1– x Ti x O 2 ( x = 0.05, 0.1), as confirmed by the previous Rietveld refinement analysis. Therefore, c -LiTiO 2 was preferred as a secondary phase in o -LiMn 1– x Ti x O 2 ( x = 0.05, 0.1) over m -Li 2 TiO 3 due to the partial loss of oxygen ions and preference for the cubic crystal structure during the synthesis (Figure c).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Given that the crystal structure and transition-metal (Ti or Mn) oxidation state of m -Li 2 TiO 3 (β phase) are similar to those of m -Li 2 MnO 3 , we considered whether m -Li 2 TiO 3 could be formed as a secondary phase in o -LiMn 1– x Ti x O 2 ( x = 0.05, 0.1). However, according to the literature, c -Li 2 TiO 3 (γ phase) is more stable than m -Li 2 TiO 3 at high temperatures (≤1050 °C). , In addition, there are a significant number of oxygen vacancies in o -LiMn 1– x Ti x O 2 ( x = 0.05, 0.1), as confirmed by the previous Rietveld refinement analysis. Therefore, c -LiTiO 2 was preferred as a secondary phase in o -LiMn 1– x Ti x O 2 ( x = 0.05, 0.1) over m -Li 2 TiO 3 due to the partial loss of oxygen ions and preference for the cubic crystal structure during the synthesis (Figure c).…”
Section: Resultssupporting
confidence: 64%
“…However, according to the literature, c-Li 2 TiO 3 (γ phase) is more stable than m-Li 2 TiO 3 at high temperatures (≤1050 °C). 56,57 In addition, there are a significant number of oxygen vacancies in o-LiMn 1−x Ti x O 2 (x = 0.05, 0.1), as confirmed by the previous Rietveld refinement analysis. Therefore, c-LiTiO 2 was preferred as a secondary phase in o-LiMn 1−x Ti x O 2 (x = 0.05, 0.1) over m-Li 2 TiO 3 due to the partial loss of oxygen ions and preference for the cubic crystal structure during the synthesis (Figure 3c).…”
Section: Transition-metal Oxidation States Of O-limn 1−x Tisupporting
confidence: 74%
“…Based on the foregoing, the purpose of this work is to study the effect of the phase composition of Li 2 ZrO 3 ceramics obtained by solid-phase synthesis and annealed at different annealing temperatures in the range from 600 to 1100°C on the strength and thermophysical parameters of ceramics. This work is part of a cycle of works devoted to the study of the Li 2 ZrO 3 ceramic properties and evaluation of the possibility of their use as blanket materials for tritium propagation, which is one of the promising research areas in modern energy [18][19][20]. Li 2 ZrO 3 ceramics were chosen as objects of study, which, as was shown earlier in [18][19][20], are highly resistant to radiation damage.…”
Section: Introductionmentioning
confidence: 99%
“…This work is part of a cycle of works devoted to the study of the Li 2 ZrO 3 ceramic properties and evaluation of the possibility of their use as blanket materials for tritium propagation, which is one of the promising research areas in modern energy [18][19][20]. Li 2 ZrO 3 ceramics were chosen as objects of study, which, as was shown earlier in [18][19][20], are highly resistant to radiation damage.…”
Section: Introductionmentioning
confidence: 99%